Pengaruh Keterangan Ahli Terhadap Keyakinan Hakim dalam Putusan Tindak Pidana Korupsi - Dilaga, Auria Patria (Unnes Law Journal: Jurnal Hukum Universitas Negeri Semarang, 2013)
The purpose of study to determine what the facts are revealed when expert testimony presented in the trial of corruption cases and to find out how the experts position to influence the judge in the decision of conviction corruption cases. Research in writing is a juridical sociological method is a qualitative approach. With the data source is primary data and secondary data. Data collection techniques used are: 1) The study of literature, 2) Observation, 3) Interview. The results of this research are: 1) The fact revealed when expert testimony presented at the hearing was related to its particular expertise so get persesuian with other evidence to assist the judge in settling cases. 2) Position the experts as well as other evidence, but it has a function in making light of the case as presented expert testimony from the trial court gave the judge his expertise gained an understanding of the whole case. The conclusions of this research are: 1) The fact that is expressed in the form of expert opinions that can help judges resolve cases duntuk because experts have different skills and competencies delivered testimony also differed among the experts. 2) Position the experts in corruption cases be generalized to other evidence, but the Criminal Code has the role of expert testimony to clarify or make light of a case.